Cultivating Proactive Career Behavior: The Role of Career Adaptability and Job Embeddedness - Peng, Peng; Song, Yu; Yu, Guangtao (Frontiers in Psychology, 2021)
Scholars have widely acknowledged that proactive career behavior is essential for individuals to proactively build their career, as well as facilitate positive career outcomes. However, there are still many questions about how to activate proactive career behavior. In the current study, we consider whether, how, and when individuals’ regulatory focus would evoke proactive career behavior. Based on career construction theory, we utilized the career adaptability framework to develop and test the mediating effect of individual regulatory focus on proactive career behavior through career adaptability. Moreover, we further proposed that job embeddedness plays as a contingency role in moderating the extent to which regulatory focus contributing to proactive career behavior with the mediation of career adaptability differently and uniquely. Using a sample of 247 participants and collecting data in three waves, we found that employees’ promotion focus positively influences their proactive career behavior through the mediation of career adaptability. Furthermore, the indirect effect of promotion focus on proactive career behavior via career adaptability was moderated by the dichotomy of individuals’ job embeddedness respectively and differently. Specifically, the positive relationship between promotion focus and proactive career behavior which was mediated by career adaptability was strengthened by employees’ on-the-job embeddedness, whereas weakened by their off-the-job embeddedness. The overall findings broaden our understanding in terms of the underlying mechanism of proactive career behavior, suggesting that individuals’ promotion focus fosters proactive career behavior via career adaptability, and on-the-job and off-the-job embeddedness as contingency factors alter the effect of career adaptability.